Incorporating the Perspectives of Disabled African Adults and Parents of Disabled African Children in Aotearoa New Zealand's Healthcare System Design - Hassan-Osman, Osman (Auckland University of Technology, 2025)
The purpose of this study was to explore the experiences of African people with disabilities and African parents of children with disabilities with healthcare services in Aotearoa New Zealand. Although participation in healthcare system design in Aotearoa New Zealand is known to improve health outcomes for communities involved, little is known about the experiences of African people with disabilities and African parents of children with disabilities. In recent years, new government departments and ministries have been established to increase the participation of people with disabilities and ethnic¹ minorities. However, none of these discussions have addressed the participation of African people with disabilities. This showed that the narratives about an inclusive society did not necessarily address the cultural barriers that African people with disabilities face in Aotearoa New Zealand, including healthcare services. To explore this gap, a qualitative case study was conducted in the North Island of Aotearoa New Zealand, Auckland, and Waikato, to shed light on the experience of African people with disabilities and African parents of children with disabilities in the healthcare system. The case study included a focus group in Auckland with three adults who identify as African and live with disabilities. They shared personal stories about what it means to be African and live in Aotearoa New Zealand. Additionally, individual face-to-face interviews were conducted with two of the same focus group participants to focus specifically on their experiences of living with disabilities. This approach respected the participants' privacy, as discussions about disabilities were not always appropriate in a group setting. The case study also included African parents of children with disabilities. Individual online interviews were conducted to explore their experiences with healthcare services in the Waikato region of Aotearoa New Zealand. The semi-structured interview questions did not focus on their children's disabilities; instead, they centred on the parents' experiences with healthcare services and their perspectives on what an intersectional approach to healthcare system design would look like. The research used intersectionality as a theoretical framework, social constructionism as a philosophical position underpinning the data gathered in the focus group and individual interviews were analysed using narrative analysis. Through narrative analysis, a number of themes and subthemes were generated. Under the main theme of being African, subthemes were being part of Aotearoa New Zealand society, being diverse, and being collective. Several sub-themes emerged from the main theme of cultural barriers to the participants' access to appropriate healthcare services in their respective regions. These sub-themes were lack of appropriate community organisation for African and Muslim people with disabilities, lack of control over their disability support, lack of agency, lack of awareness of disability resources, and perception of discrimination. ¹The term “ethnic,” in the context of this research, refers to those who are migrants, refugees, long-term settlers, and those who identify as Asian, Continental European, Middle Eastern, Latin American, and African, regardless of their birth country (Nakhid, 2016)